70 Atrial fibrillation is associated with long-term mortality in patients undergoing surgical aortic valve replacement. (17th July 2020) - Farag, Mohamed; Peverelli, Marta; Reddy, S Ashwin; Spinthakis, Nikolaos; Osman, Mohamed; Sullivan, Keith; Gorog, Diana A; Krishnan, Unni; Nashef, Samer
Abstract : Introduction: Atrial fibrillation (AF) is common in patients with aortic valve disease, although the exact mechanism is unclear. New-onset AF is frequent after any open-heart surgery, but evidence suggests it may have no significant impact on survival if sinus rhythm (SR) is effectively restored early after the onset of the arrhythmia and before hospital discharge. In contrast, management of preoperative persistent AF is often overlooked during or after open-heart surgery despite several proposed protocols. This study sought to evaluate the impact of preoperative persistent AF on mortality in patients undergoing isolated surgical aortic valve replacement (AVR). Methods: Retrospective, single-centre study involving 2, 628 consecutive patients undergoing elective primary isolated AVR from 2008 to 2018. A total of 268/2, 628 patients (10.1%) exhibited persistent AF before surgery. The effect of preoperative AF on long-term mortality was evaluated with univariate and multivariate regression analyses. Results: Statistically significant differences were observed in patients' age, history of hypertension, diabetes, myocardial infarction, preoperative creatinine level, left ventricular function and EuroSCORE between AF and SR groups [Table 1 ]. In-hospital mortality was 0.8% and was not different between AF and SR groups. AF was highly predictive of long-term mortality (median follow up of 4 years [IQR 2-7]; HR: 2.24, 95% CI: 1.79–2.79, p=<0.001) [Figure 1 ], and remained strongly and independently predictive after adjustment for other risk factors (HR: 1.54, 95% CI: 1.23–1.94, p=<0.001). Other independent predictors of long-term mortality included advanced age, presence of diabetes, chronic pulmonary disease, peripheral vascular intervention, poor left ventricular function and elevated preoperative creatinine level. Conclusions: The presence of preoperative AF in patients undergoing isolated AVR was affected by many risk factors and was associated with a higher EuroSCORE. Preoperative AF was independently predictive of long-term mortality in this cohort. It remains to be seen whether concomitant surgery or other preoperative measures to correct AF may impact long-term outcomes. Conflict of Interest: None